INCIDENCE OF BLUETONGUE IN SHEEP IN PUDUKKOTTAI DISTRICT OF TAMIL NADU - Balakrishna, G; Thaigarajan, R; Gopi, H; Paramsivam, A; Babu, M (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Occurrence of Bluetongue in 4 flocks of sheep in Pudukkottai district of Tamil Nadu during the year 2003 was confirmed by AGID. The clinical signs observed were fever (410C), bloody nasal discharge, ulcers in tongue and gums, wry neck and coronitis. 40% morbidity and 10% mortality were recorded. Isolation and treatment of sick animals resulted in recovery of normal health in the flock. Rain suspected to be a predisposing factor in this outbreak.